Hubungan Bentuk Papilla Ibu Menyusui dengan Keberhasilan Ibu Menyusui Bayi Usia 0-24 Bulan - Yeyen Desiar Firdasary (NERSMID : Jurnal Keperawatan dan Kebidanan, 2019)
Papilla or nipple, which is a prominent part in the nipples. Categorized papilla shape protruding and not protruding, the shape of the papilla which does not protrude affect optimal breastfeeding fails to affect milk production further reluctant baby suckle and affect breastfeeding success. The purpose of this study was to determine the relationship of papilla form successful breastfeeding nursing mothers with babies aged 0-24 months. This type of research is analytic research. The population is all lactating mothers of infants aged 0-24 months as many as 90 people. The sampling technique random sampling obtained a sample of 48 respondents. This study was conducted in March 2017. The collection of data through observation. The independent variable is the form papilla breastfeeding mothers, while the dependent variable is the success of breastfeeding infants aged 0-24 months. Data were analyzed using Chi Square test with α = 0.05. The results showed that 26 respondents (54.2%) form prominent papillae nursing mothers. While successful breastfeeding of infants aged 0-24 months 25 respondents (52.1%) in the category of work. The result of Chi Square test with df 1 with α = 0.05 results obtained p-value = 36.778 compared with 1 df table table value = 3.841 Chi Square count the results of larger tables, There is a relationship between the shape of the papilla nursing mothers with breastfeeding success infants aged 0-24 months in the village of billowing, District Kertosono, Nganjuk Year 2017. Based on the above data it can be concluded that the success of breastfeeding is influenced by the shape of the papilla nursing mothers, nursing mothers are advised care in order to achieve successful breast feeding.